WorldView-2 sensor for the detection of hematite and goethite in tropical soils - Baptista, Gustavo Macedo de Mello; Teobaldo, Débora (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to simulate the bands of the WorldView-2 sensor from laboratory specters, in order to study its potential to detect iron oxides, besides proposing a spectral index based on the depth of the spectral feature (RHGtPf). The iron index (IFe) and the hematite index (IHm), developed by Madeira Netto for bands of Landsat TM-5 sensor, were adjusted for WorldView-2 to test the potential of the new yellow band. The results showed that the yellow band degrades to 2% compared to the red one. This is due to fact that mineral quantification and identification are in the absorption feature, not in the reflectance one, and it is only improved in the visualization of color. A new spectral index, the RHGtPF, based on the depth feature with the continuum-removed spectra, was proposed, since the new bands of the WorldView-2 sensor – the coastal blue and yellow bands – allow a better individualization of the absorption features for goethite and hematite separately. The new index is statistically similar to the ratio Hm / Gt + Hm; however, it is not similar to the mineralogical relation obtained with Munsell colors.